Differences Of Dental And Mouth Pregnancy Hygiene In Tunggulo West Limboto Village Gorontalo District 2015 - mustapa Bidjuni (Faculty of Public Health, Andalas University, 2017)
Oral hygiene in pregnant women is crucial. This is caused when pregnant occur hormonal and physiological changes. Fluctuations in the hormones estrogen and progesterone effect on liquid servikular, serum, saliva, and gingiva tissue, as well as the presence of dietary changes, lack of oral hygiene, nausea, vomiting and dental erosion. This study aim to analyze differences of OHI-S on pregnant women trimester I, II and III. This study design was cross-sectional study of 47 people were taken by total sampling. Statistic analysis using paired samples t-test. Result of univariate analysis shows the number of respondents is most pregnant women trimester II and III. Results of bivariat analysis have significant differences between OHI-S trimester I and II (t = 3.792 > t table), I and III trimester (t=6,686 > t table) and the II and III trimester (t=2,650 > t table) with (p < 0.05) on pregnant women in the Tunggulo West Limboto Village Gorontalo District. There is difference of oral hygiene every trimester pregnant women. The suggestion of dental health education is given about how to maintain oral health i.e. brushing teeth at least twice daily after breakfast and before bed nights and check up at least twice a year.